Электродиализная очистка воды в магнитном поле - Цхе А. А. Александр Алексеевич; Мышкин В. Ф. Вячеслав Фёдорович; Дорофеева Л. И. Людмила Ивановна; Камытбаева А. У.; Перминов С. В.; Хан В. А. Валерий Алексеевич (2013, 2013)
В фонде НТБ ТПУ отсутствует